Development of Learning Material for Newcomers to Field of AI - Takesako, Hayato; Inoue, Akira (2020 IEEE 2nd International Conference on Artificial Intelligence in Engineering and Technology (IICAIET), 2020)
In light of the social background in which the demand for AI human resources with basic knowledge and skills related to AI has increased in recent years due to the development of AI technology, this study proposes a newly developed learning material for beginners in the AI field. It consists of material for learning basic AI-related knowledge and for developing AI easily through a visual programming tool that uses Scratch. We conducted an evaluation experiment on university students and verified its characteristics as suitable material for learning AI. We perform an understanding level check test on AI before and after using the teaching material and analyze the level of understanding about AI from the difference between the average scores. In addition, we analyze the feeling of use of the teaching materials from two evaluations: an ARCS motivational model and a free description sentence from the subject. The results of the evaluation experiment indicated that this teaching material promoted the subjects interest in AI and their acquisition of basic AI-related knowledge and is therefore suitable for teaching beginners in the field of AI.